KOMUNIKASI PEMASARAN DAN PERILAKU KONSUMEN DI MATAHARI DEPARTMEN STORE MEGA TRADE CENTER MANADO (ACTA DIURNA KOMUNIKASI, 2015)
This study took the title of Communication Consumer Behavior and Marketing Communication in the Sun Department Store Mega Trade Center Manado. Initially the shopping center in the city of Manado concentrated around Park National Unity (TKB) or Market '45. Along with the economic growth of the city of Manado, within recent years, industrial and retail properties in Manado growing quite rapidly. Starting from coastal reclamation projects undertaken for 10 years, was built after the road by the beach or boulevard was inaugurated in 1993 with Jalan Piere Tendean or better known as Manado Boulevard. For these reasons then the Matahari Department Store continues to perform marketing communication regarding the current products with a combination of face-to-face sales (direct selling), advertising on television and in newspaper advertising and sales promotion. The third way of marketing communications is then combined with the contents of the message on the promotion of a massive discount. Through observations with interviews with management in Meda Trade Center Manado Matahari Department Store shopping habits of people usually follow the example on religious feast days (Christmas, New Year, Eid, Chinese New Year) but also the days of big state like tujuhbelasan, day-to-day specials like valentine day and at the end of each month, but all the activities or the discount program is national because of competition with other similar retail companies are also increasingly stringent.To be successful in sales, the company must have a marketing communication tips. Communication itself according to Susanto (1977: 8) is the process of delivering opinions, thoughts, and feelings of a person or group of persons on others. These definitions mean in communication, delivery of messages from the communicator will result in changes in behavior.Matahari Department Store continues to communicate the advantages of its products, including the presence of the lure of big discounts are continuously carried out by the sun. Such as communication in general, marketing communications bertumpuh on the dissemination of information (messages) about products owned by persuasive communication techniques to remind or persuade because the competition is so tight with known businesses scattered similar in Manado City, especially in the area of the boulevard.The method used is the method description only describes a situation or event. This study did not look for or explain, the relationship does not test hypothesis or make predictions. Description of research by many investigators called survey research. Descriptive study purpose is to create a description, picture, or painting in a systematic, factual and accurate as well as the facts, the properties and the relationship between the phenomenon investigated.From the research that has been described in the previous chapter it is clear that marketing communications activities through marketing messages by PT. Matahari Department Store instrumental in influencing consumer behavior. AbstrakAwalnya pusat perbelanjaan di Kota Manado terkonsentrasi di seputar Taman Kesatuan Bangsa (TKB) atau Pasar ‘45. Seiring dengan pertumbuhan ekonomi kota Manado, dalam kurun waktu beberapa tahun belakangan ini, industri properti dan retail di Manado berkembang cukup pesat. Bermula dari proyek reklamasi pantai yang dilakukan selama 10 tahun lebih, dibangun setelah jalan tepi pantai atau boulevard diresmikan tahun 1993 dengan Jalan Piere Tendean atau lebih dikenal dengan Manado Boulevard. Dengan alasan tersebut kemudian pihak Matahari Departement Store terus melakukan komunikasi pemasaran mengenai produk-produk terkini dengan kombinasi penjualan tatap muka (direct selling), iklan di televisi dan iklan di surat kabar dan promosi penjualan. Ketiga cara komunikasi pemasaran ini kemudian dikombinasi dengan isi pesan mengenai promosi diskon besar-besaran. Melalui pengamatan disertai wawancara dengan pihak manajemen di Mega Trade Center Manado Matahari Departement Store biasanya mengikuti kebiasaan masyarakat berbelanja contoh pada hari-hari raya keagamaan (natal, tahun baru, lebaran, imlek) tapi juga hari-hari besar kenegaraan seperti tujuhbelasan, hari-hari spesial seperti valentine day dan pada setiap akhir bulan, tapi semua kegiatan atau program diskon tersebut bersifat nasional karena persaingan dengan perusahaan ritel sejenis juga semakin ketat.Agar sukses dalam penjualan, perusahaan harus memiliki kiat-kiat komunikasi pemasaran. Matahari Departement Store terus berupaya mengkomunikasi kelebihan-kelebihan produknya termasuk dengan adanya iming-iming diskon besar-besaran yang secara kontinue dilakukan pihak matahari. Seperti komunikasi pada umumnya, komunikasi pemasaran bertumpuh pada penyebaran informasi (pesan) mengenai produk-produk yang dimiliki dengan teknik komunikasi persuasif untuk mengingatkan atau membujuk karena diketahui persaingan begitu ketat dengan usaha-usaha serupa yang bertebaran di Kota Manado khususnya di kawasan boulevard.Metode yang digunakan adalah metode deskripsi yang hanya memaparkan situasi atau peristiwa. Penelitian ini tidak mencari atau menjelaskan, hubungan tidak menguji hipótesis atau membuat prediksi. Penelitian deskripsi oleh banyak peneliti disebut juga penelitian survei.Hasil penelitian yang sudah dipaparkan di bab sebelumnya jelas bahwa kegiatan komunikasi pemasaran melalui pesan-pesan pemasaran yang dilakukan PT. Matahari Departemen Store cukup berperan dalam memengaruhi perilaku konsumen.